Порівняльна характеристика властивостей та принципів права (теоретико-правовий аспект) - Біржакова, Є.О. (Альманах права, 2012)
В статті досліджуються основні категорії права: його властивості об’єктивного характеру та основоположні засади — принципи. Визначаються їх спільні та відмінні риси. Порівняльний аналіз принципів та властивостей права здійснюється на прикладі такої складної та багатогранної категорії, як «справедливість». В статье исследуются основные категории права: его свойства объективного характера и основоположные идеи — принципы. Определяются их общие и отличительные черты. Сравнительный анализ принципов и свойств права осуществляется на примере такой сложной и многогранной категории,
как «справедливость». The law is a difficult and multidimensional category. The important aspect of research of law as a scientific category is a determination of its nature, essence and social setting. The analysis of modern law in the process of its forming, functioning and realization, unavoidable appears as a difficult intensive cognitive process. In the article are examined the major categories of law, among which its properties in objective nature and the founding ideas — principles. Properties of law are considered as necessary structural characteristics of law which in its totality make quality of the law and give possibility to describe law as integral, independent phenomenon in objective reality. Properties of law are in unity, dialectical co-operation and combination. Properties of law provide it to ensure high increase in organization of public relations, making them well-regulated and the order. Principles of law are considered by author as the fundamental idea which is governed by law. Principles of law have an universal value, designed in industry of basic human rights and got fixing at an international level. The author comes to the conclusion that principles of law are derivative from its properties. It means that the properties of the law objective character are primary characteristics of law as phenomenon of social reality. In the article are also considered general signs of properties and principles of the law among which, in particular: the need to define various aspects of the manifestation of both categories; implementation of these categories in public practice and their impact on the effectiveness of legal regulation; specificity of properties and principles of law in the plane of different approaches to legal understanding, as well as the universal nature some of them in the aspect of consideration as a natural or positive legal understanding, etc. The comparative analysis of properties and principles of law is carried out on the example of such complex and multifaceted category as «justice». An author concludes that justice is not just a principle of law, namely its property.